Gender identity and wives' labor market outcomes in West and East Germany between 1984 and 2016 - Maximilian Sprengholz; Anna Wieber; Elke Holst (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
We exploit the natural experiment of German reunification in 1990 to investigate if the institutional regimes of the formerly socialist (rather gender-equal) East Germany and the capitalist (rather gender-traditional) West Germany shaped different gender identity prescriptions of family breadwinning. We use data for three periods between 1984 and 2016 from the representative German Socio-Economic Panel (SOEP). Density discontinuity tests and fixed-effects regressions suggest that married couples in West (but not East) Germany diminished the wife's labor market outcomes in order to avoid situations where she would earn more than him. However, the significance of the male breadwinner prescription seems to decline in West Germany since reunification, converging to the more gender-egalitarian East Germany. Our work emphasizes the view that political and institutional frameworks can shape fairly persistent gender identity prescriptions that influence household economic decisions for some time, even when these frameworks change.
Keywords: J16; J12; D10; 330; Gender identity; Male breadwinner norm; Institutions; Female labor market outcomes; SOEP